2020
DOI: 10.1002/celc.202000171
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Reduction of [Ni(Mebpy)3]2+: Elucidation of the Redox Mechanism by Cyclic Voltammetry and Steady‐State Voltammetry in Low Ionic Strength Solutions

Abstract: Bipyridine complexes of Ni are used as catalysts in a variety of reductive transformations. Here, the electroreduction of [Ni(Mebpy)3]2+ (Mebpy=4,4′‐dimethyl‐2,2′‐bipyridine) in dimethylformamide is reported, with the aim of determining the redox mechanism and oxidation states of products formed under well‐controlled electrochemical conditions. Results from cyclic voltammetry, steady‐state voltammetry (SSV) and chronoamperometry demonstrate that [Ni(Mebpy)3]2+ undergoes two sequential 1e reductions at closely … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 17 publications
1
14
0
Order By: Relevance
“…Finally, we thought that the stability of Ni­(II)–acyl complex I would provide an interesting opportunity to get further insights into the reactivity of electroreduced monovalent Ni–acyl complex toward alkyl and acyl electrophiles (Figure ). In particular, Ni­(I) intermediates have been recently proposed to be the most relevant catalytically active species in cross-coupling reactions under reductive conditions, but very less mechanistic information has been gained on the electrophile activation step at Ni­(I). ,,,, …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, we thought that the stability of Ni­(II)–acyl complex I would provide an interesting opportunity to get further insights into the reactivity of electroreduced monovalent Ni–acyl complex toward alkyl and acyl electrophiles (Figure ). In particular, Ni­(I) intermediates have been recently proposed to be the most relevant catalytically active species in cross-coupling reactions under reductive conditions, but very less mechanistic information has been gained on the electrophile activation step at Ni­(I). ,,,, …”
Section: Resultsmentioning
confidence: 99%
“…This has been substantiated with electro-generated Ni­(I)–OAc and Ni­(I)–acyl intermediates; (ii) stoichiometric studies have shown that C–N bond oxidative addition of alkyl N -acyl imides also readily proceeds at Ni(0) species to give isolable Ni­(II)–acyl imidate species. The succinimidate ligand was shown to provide enhanced stability to the Ni­(II)–acyl intermediate, allowing us to evidence its catalytic relevance; (iii) under reductive electrolysis of ( t Bubpy)­Ni­(OAc) 2 , the predominant species responsible for the activation of both electrophiles are Ni­(I) …”
Section: Discussionmentioning
confidence: 99%
“…Recent mechanistic studies using voltammetric studies show the viability of a sequential two-electron reduction of Ni(II) to Ni(I) and Ni(0), thus, providing the possibility of aryl halide activation via oxidative addition of Ni(I) or Ni(0). 12 The ability of metal-catalyzed electrosynthesis in controlling redox states of the catalyst allows the transformation to preclude the use of highly air-sensitive M(0) catalysts and phosphine ligands as well as access to the desired Ni(III) intermediates. As such, the reactions can be performed at room temperature and in air.…”
Section: Transition Metal Electrocatalysismentioning
confidence: 99%
“…An anodic oxidation of the aryl-Ni­(II)-amine complex generates the reactive aryl-Ni­(III)-amine intermediate that can readily undergo reductive elimination at room temperature. Recent mechanistic studies using voltammetric studies show the viability of a sequential two-electron reduction of Ni­(II) to Ni­(I) and Ni(0), thus, providing the possibility of aryl halide activation via oxidative addition of Ni­(I) or Ni(0) …”
Section: Introductionmentioning
confidence: 99%
“…The electrocatalytically relevant pathways involve the subsequent expulsion of bipyridine (at moderate rate of ca. 10 s –1 for [Ni II (Me 2 bpy) 3 ] 2+ ) 97 that produces a more stable tetracoordinated Ni(0) [Ni 0 (R 2 bpy) 2 ] species ( Figure 12 ).…”
Section: Case Studiesmentioning
confidence: 99%